“Rending the veil of space and time asunder”: Percy Shelley’s Poetics of Event(s) in Ode to Liberty - Hortolland, Pauline (Romanticism on the Net, 2020)
This paper explores Shelley’s complex response to the tradition of the progress poem in Ode to Liberty, a poem published in August 1820 with Prometheus Unbound which celebrates the fall of absolute monarchy in Spain in January 1820. My contention is that Shelley destabilizes the conception of gradual progress which generally underpins the progress poem, ultimately suggesting that the origin of Liberty is not to be found in chronological time, but in human potentiality. I also argue that the poem tends to blur the difference between representing historical events and presenting itself as an event. This makes explicit the ambition of the progress poem to become itself an event in its own right, that is, a revelation of a secret world order that enables us to form a legible history out of the apparent chaos of events. Yet, the order unveiled in Shelley’s poem proves a decidedly personal and poetic one which does not fit the traditional narratives of progress and empire usually associated with this period. In the last part of the article, I rely on Agamben’s reflection on the act of creation in The Fire and the Tale (2017) to give a new reading of the poem’s ending, which has often been interpreted as an example of the unresolved struggle between political idealism and skepticism in Shelley’s poetry.